2019
DOI: 10.3390/met9060631
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deep Cryogenic Treatment on Microstructure and Properties of 7A99 Ultra-High Strength Aluminum Alloy

Abstract: The hardness, toughness, wear resistance, and fatigue behavior of materials can be improved through a deep cryogenic treatment (DCT). During this treatment, low temperatures (−100 °C to −196 °C) are maintained and then increased to room or higher. In this work, an indirect-extrusion plate of 7A99 ultra-high strength aluminum alloy was subjected to a T6 (peak aging) treatment and a T6-DCT treatment. The influence of the T6-DCT treatment on the mechanical properties, grain morphologies, precipitates, and atom–cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The DCT is equivalent to a special aging treatment, which can accelerate the later aging process and lead to more and finer precipitates. [ 25 ] The effect of DCT on later aging treatment is mainly reflected in the increase in the diffusion rate of Zn and Mg atoms due to the rapid increase of temperature and the formation of the GP region of solute atoms during the DCT. The GP region of solute atoms with sufficient size can act as the center for later nucleation, high energy dislocations can also act as the nucleation center of solute atoms, so the nucleation rate of precipitates is improved.…”
Section: Discussionmentioning
confidence: 99%
“…The DCT is equivalent to a special aging treatment, which can accelerate the later aging process and lead to more and finer precipitates. [ 25 ] The effect of DCT on later aging treatment is mainly reflected in the increase in the diffusion rate of Zn and Mg atoms due to the rapid increase of temperature and the formation of the GP region of solute atoms during the DCT. The GP region of solute atoms with sufficient size can act as the center for later nucleation, high energy dislocations can also act as the nucleation center of solute atoms, so the nucleation rate of precipitates is improved.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum alloys 7xxx series are using in many engineering applications, such as aerospace and aircraft structures and recently in the military field [1,2]. Alloy 7001 is an alloy, with zinc as the primary alloying element; it has high mechanical and corrosion resistance and excellent fatigue life due to precipitation hardened.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Results indicated that the pitting does not significantly influence fatigue performance. Others have examined the influence of (DCT) on the properties of aluminum alloys, [2] have investigated the improvement in hardness, toughness, wear resistance, and fatigue life on an extruded plate of high strength Al 7A99 alloy using (T6) treatment (The T6 thermal cycle consists of a solution heat treatment followed by a water quenching and then an age hardening (or precipitation hardening) then by (T6+DCT) treatment. After the T6 (peak ageing) method.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A deep cryogenic treatment with a long soaking time (45 h) had positive effects on the mechanical properties and machinability of a 5083 alloy [14]. Gao et al [15] also found that deep cryogenic treatment improved the strength and plasticity of a 7A99 alloy through refining the precipitates and increasing the uniformity of the precipitate distribution. Park [16] revealed that cryogenic treatment followed by rapid reheating (uphill quenching) released the residual stress and obviously improved the tensile properties.…”
Section: Introductionmentioning
confidence: 98%